PENGARUH BENTUK DASAR DAN ORIENTASI BANGUNAN TERHADAP BEBAN ENERGI PADA BANGUNAN BERTINGKAT DI JAKARTA - GERVASIUS HERRY PURWOKO (Faculty of Humanities and Creative Industries, Maranatha Christian University (formerly Faculty of Fine Arts and Design), 2017)
Due to expensive energy costs nowadays, the architects are demanded to produce relatively efficient building designs, especially those with many stories. As a consequence, both accurate estimation and energy saving measures are extremely needed even at the early stage of the planning process. In fact, the consumption for the building energy has been mostly absorbed by air conditioning and lighting needs. In practice, both of them have been affected by direct contact of the sunlight penetrating through the building casing, either by conduction, convection or radiation processes. While both shapes and positions of the building casing are very much dependent on the basic shapes and the building orientation, a critical question is needed to investigate any further: to what extent each basic shape of the buildings is likely to increase or decrease the energy and which orientation gives significant effects. Designed in an experimental research, this study aims to investigate the characteristics of the building shapes in obtaining the heat and to examine the total energy consumption. A series of testing measures is conducted by changing the building basic shapes and their orientation according to the basic conditions previously set. In so doing, obtaining calculated energy consumption difference could be achieved. It is expected that the results of this study is worth considering reference for architects and hence they are able to determine appropriate building basic shapes as well as their appropriate orientation during the planning phase. Â Keywords: building basic shapes; building energy; orientation; sunlight